Reducing The Power Consumption of The CMOS CISC Processor by Reducing The Transitions between 0 and 1 in The Control Unit - Naal, Mouhamad Ayman; Bouchi, Amer; Shaheen, Toulai AbdAlkader (Journal of engineering sciences and information technology, 2022)
Power consumption is very important in digital design. Many portable devices, such as cell phones, laptops and personal-use medical devices, use battery as energy source. To design low-power processor, a number of techniques were developed, such as clock gate, power gate, and architectural redesign of parts of the processor. In addition to hardware techniques, the software as well can affect the power consumption. To reduce energy consumption, it is necessary to choose the factor that affect the energy consumption of a program. An important factor of power consumption of CMOS circuits is the rate of switching between 0 and 1. This papers presents a new design of the control unit of the processor which reduces the 0, 1 transitions during the program execution, and so reduces the energy consumption of the processor. To achieve this objective, a deep study of the design of the microprogramming of x86 assembly language instruction set is conducted. The new control unit save by 7.81%.